Flammulina velutipes polysaccharide-iron(III) complex used to treat iron deficiency anemia after being absorbed via GLUT2 and SGLT1 transporters - Chenying Shi; Chen Cheng; Xiaotong Lin; Yanfang Qian; Yufeng Du; Guitang Chen (Food Science and Human Wellness)
Iron deficiency anemia (IDA) is a common nutritional problem, but traditional iron supplements cause many adverse reactions. Thus, the development of a novel iron supplement might be significant for the treatment of IDA. This study aimed to study the transport mechanism of Flammulina velutipes polysaccharide-iron complex (FVP1-Fe(III)) in Caco-2 cells and the therapeutic effect on IDA rats, as well as the influence on gut microbiota in vivo. These results showed that in vitro, the uptake of FVP1-Fe(III) was mediated by sodium-dependent glucose transporter-1 (SGLT1) and facilitated glucose transporter-2 (GLUT2) and GLUT2 played a dominant function. The multidrug resistance-associated protein-2 (MRP-2) was involved in the efflux of FVP1-Fe(III) across the Caco-2 cells. In vivo, FVP1-Fe(III) had a better restorative effect on blood parameters and iron status indicators in rats with IDA as compared with FeSO4 and exerted this effect by downregulating the expression of hepcidin. FVP1-Fe(III) could also regulate gut microbiota dysbiosis in iron deficiency rats by returning the relative abundance of gut microbiota to the normal level. Besides, as a dietary factor, vitamin C (vit C) could enhance the therapeutic effect of FVP1-Fe(III). These present findings showed that FVP1-Fe(III) could be exploited as a novel iron supplement to treat IDA.